A survey of Diphya Nicolet, 1849 (Araneae: Tetragnathidae) from South Africa - Omelko, Mikhail M.; Marusik, Yuri M.; Lyle, Robin (Zootaxa, 2020)
In this paper, five species of Diphya Nicolet, 1849 are recognized in the fauna of South Africa. Four of these species are new: D. foordi sp. nov. (♂♀), D. leroyorum sp. nov. (♂), D. vanderwaltae sp. nov. (♀) and D. wesolowskae sp. nov. (♂♀). The male of D. simoni Kauri, 1950 is described for the first time. Diphya tanikawai Marusik, 2017 syn. nov. was found to be a junior synonym of D. simoni. Descriptions with illustrations, photographs and SEM images are provided for all species. The relationship between the South African and the Neotropical Diphya species is briefly discussed.